High energy density carbon–cement supercapacitors for architectural energy storage - Damian Stefaniuk; James C. Weaver; Franz-Josef Ulm; Admir Masic (Proceedings of the National Academy of Sciences, 2025)
Electron-conducting carbon concrete (ecˆ3) is a multifunctional cement-based composite material that combines mechanical robustness with electrochemical energy storage. To further expand our understanding of structure–function relationships in this complex multiphase material system and provide a roadmap for transitioning this technology from a simple proof-of-concept to a viable large-scale energy storage alternative, we report insights into the nanoscale connectivity of the electrode’s conductive carbon network, explore different electrolyte compositions and material integration strategies, and highlight opportunities for device scaling. Through the use of FIB-SEM tomography, the electrode’s percolating fractal-like nano-carbon black network has been visualized at the nanoscale, providing insights into the theoretical energy storage capacity of this material. To reduce the required times for the production of functional electrodes, we also present a cast-in electrolyte approach, where centimeter-thick electrodes could be produced without the need for postcuring steps. In these prototypes, device performance scales linearly with electrode thickness and cell count, and a simple analytical model was developed to explain these scaling phenomena. Furthermore, the exploration of alternative ionic and organic electrolytes further contribute to improved electrochemical behavior, with the fabricated designs ultimately achieving a 10-fold increase in supercapacitor energy density compared to previous designs. Finally, we were able to fabricate a 12 V, 50 F supercapacitor module and a 9 V arch prototype that integrate energy storage into load-bearing architectural elements. These functional prototypes highlight the potential for real-time structural health monitoring, while demonstrating the potential of our ecˆ3 technology for the production of a scalable, high-voltage concrete energy-storing infrastructure.